Detection and classification of islanding and power quality disturbances in microgrid using hybrid signal processing and data mining techniques. Issue 1 (1st February 2018) - Chakravorti, Tatiana; Patnaik, Rajesh Kumar; Dash, Pradipta Kishore
Abstract : This study presents multi‐scale morphological gradient filter (MSMGF) and short‐time modified Hilbert transform (STMHT) techniques, respectively, to detect and classify multiclass power system disturbances in a distributed generation (DG)‐based microgrid environment. The non‐stationary power signal samples measured near the target DG's are processed through the proposed MSMGF and STMHT techniques, respectively, and some computations over them generates the target parameter sets. Depending on the complexity of the overlapping in the target attribute values for different disturbance patterns, fuzzy judgment tree structure is incorporated for multiclass event classification, which proves to be robust for most of the classes. In this regard, an extensive simulation on the proposed microgrid models, subjected to a number of multiclass disturbances has been performed in MATLAB/Simulink environment. The faster execution, lower computational burden, superior efficiency as well as better accuracy in multiclass power system disturbance classification by the proposed judgment tree‐based MSMGF and STMHT techniques, respectively, as compared to some of the conventional techniques, is significantly illustrated in the performance evaluation section. Further, as illustrated in this section, the real‐time capability of the proposed techniques has been verified in the hardware environment, where the results shown are satisfactory.